ENERGY-INTENSIVE PROCESSING TECHNOLOGIES OF AGRICULTURAL PRODUCTS (Scientific journal of the Fergana State University, 2023)
This article provides an analysis of existing technologies for processing agricultural products, as well as the results of the scientific research on the creation of technologies for obtaining high-quality, competitive products.